Botswana - Kras, Sara Louise (New York : Children's Press, 2008)
Introduces children to the people, culture, geography, history, and animals of Botswana, with color photographs, original maps, interactive sidebars, fast-facts, and Internet resources to help children learn more about the country.
The gem of Africa -- From desert to delta -- Magnificent life -- Becoming Botswana -- A democratic success -- A bright future -- Living together -- Spiritual life -- Arts and sports -- Life in Botswana -- Timeline -- Fast facts.
Includes bibliographical references (p. 134) and index.
6.9
5-8
Keywords: Botswana -- Juvenile literature; Botswana; Botswana